Smart Money Moves: How Financial Literacy, Lifestyle, and Social Media Shape Student Finances - Thalia Risdianti Ardiana; Sasongko Budisusetyo (Reviu Accounting, Business & Organizations, 2026)
Research Objective - To analyze the influence of financial literacy, lifestyle, pocket money, and social media on students' personal financial management at Hayam Wuruk Perbanas University Surabaya. Research Methodology - This study employs a quantitative approach using Structural Equation Modeling - Partial Least Squares (SEM-PLS) with 154 respondents, using a Likert-scale questionnaire. Research Findings - Financial literacy, pocket money, and social media have a significant positive influence, whereas lifestyle does not show a significant effect. Social media emerges as the dominant factor (R²=0.530). Theoretical and Policy Implications - This study strengthens the Theory of Planned Behavior in digital contexts and advocates policies that promote practical financial education and social media literacy in higher education institutions. Research Novelty - This research treats digital environmental factors (social media) as the primary determinant of students' financial management, complementing traditional approaches that focus on financial literacy and resources.